Advice for athletes during Covid-19 - Breslin, G.; Lowry, R.; Lafferty, M.; Britton, D.; Morris, R.; Barker, J.; Slater, M.; Eubank, M. (British Psychological Society, 2020)
This document aims to provide psychological support and guidance for athletes during the current Covid-19 pandemic. Since 23 March, lockdown in the United Kingdom has meant extreme changes and athletes have been forced to significantly alter their training and competition routines. These changes can lead to feelings of anxiety, frustration, and anger for some, and this guidance aims to help alleviate these emotions. The Covid-19 lockdown can be called a non-normative transition in sport, this means that it was unexpected and could not be prepared for. This can make it more difficult to manage, and have negative consequences for mental health and psychological wellbeing. This Covid-19 transition will be overwhelming for some - posing many questions around the uncertainty of how long the lockdown period will last, the effect of lockdown on long-term goals for training and competition, and further doubts about what the transition process of emerging from lockdown will look like. We will offer psychological advice to help you deal effectively with the Covid-19 transition, and to place you in a better position to deal with the psychological and behavioural challenges the current situation poses, regardless of when, and if, you return to sport. Three key priorities have been identified which have been shown to be critical for managing transitions, such as the Covid-19 transition.